Evaluation of Radon Concentrations in some Samples of Dwellings of Lung Cancer Patients and Healthy Using CR-39 in Iraq - Haneen Waheed Kadhim, Heiyam Najy Hady (Pakistan Journal of Medical & Health Sciences, 2023)
Lung cancer is considered a disease that is completely happened by smoking; therefore, it is preventable perfectly. Yet, a small percentage of cases is there, possibly as many as 5 to 15%, in which there are other reasons. The risk factors acknowledged for the other groups comprise passive smoking, family history of cancer, occupational expo sure to certain chemicals and ionizing radiation, and diet. Moreover, a fifty samples from the dwelling of lung cancer patients were compared with twenty healthy volunteers. The study aims at identifying the dangers of radon gas in the dwelling of infected patients and the control group, clarifying how it contributes to increasing the risk of lung cancer. To achieve the aim of the study, the researcher used nuclear track detectors CR-39 , baguettes and TASLIMAGE System . Keywords: Lung cancer, CR-39 Detector, Radon gas for dwellings, Iraq.